Pelatihan Pembuatan Produk Kering Tanaman Obat (Simplisia) untuk Kader PKK Desa Bengkaung - Hanifa, Nisa Isneni; Hidayati, Agriana Rosmalina; Mukhlishah, Neneng Rachmalia Izzatul; Lisnasari, Baiq Risky Wahyu; Purnomo, Indra; Bayani, Faizul (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Bengkaung Village, located in Batulayar District, has abundant natural resources, but they have not been optimally utilized. One way to utilize medicinal plants is by processing them into dried products, commonly known as simplisia, which allow for more extended storage. The community lacks sufficient knowledge of proper simplisia production techniques using the simple tools available in the village. The purpose of this activity is to enhance the skills and knowledge of PKK cadres from Bengkaung Village in processing medicinal plants found around the village into dried simplisia products of high economic value. This training activity was conducted through counseling and hands-on practice in producing medicinal plant simplisia using simple technology, followed by simplisia packaging. The training ran smoothly, and participants were enthusiastic throughout the activity. The outcomes of this program include packaged medicinal plant simplisia products in attractive containers and an increase in the knowledge of proper simplisia production among PKK cadres.